2018
DOI: 10.1186/s12879-018-3120-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing behavior among general practitioners – a questionnaire-based study in Germany

Abstract: BackgroundThis study investigates the barriers and facilitators of the use of antibiotics in acute respiratory tract infections by general practitioners (GPs) in Germany.MethodsA multidisciplinary team designed and pre-tested a written questionnaire addressing the topics awareness of antimicrobial resistance (7 items), use of antibiotics (9 items), guidelines/sources of information (9 items) and sociodemographic factors (7 items), using a five-point-Likert-scale (“never” to “very often”). The questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
27
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 42 publications
11
27
2
3
Order By: Relevance
“…Interestingly, our data showed that in urbanized PCN practice locations, quinolone prescription rates were lower than in rural locations. This complements results from a previous study where German GPs working in urban areas were found to be more likely to use the strategy of delayed prescribing of antibiotics than GPs working in rural areas [8]. Such discrepancies between urban and rural prescribing habits potentially could root in more ample opportunities for self-re ection about prescribing motivated by regular peer exchange and a broader and more frequent offer of continued training and upskilling in urban locations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, our data showed that in urbanized PCN practice locations, quinolone prescription rates were lower than in rural locations. This complements results from a previous study where German GPs working in urban areas were found to be more likely to use the strategy of delayed prescribing of antibiotics than GPs working in rural areas [8]. Such discrepancies between urban and rural prescribing habits potentially could root in more ample opportunities for self-re ection about prescribing motivated by regular peer exchange and a broader and more frequent offer of continued training and upskilling in urban locations.…”
Section: Discussionsupporting
confidence: 82%
“…However, strong variations of overall and age-group-speci c distributions of antibiotic subgroups could be identi ed [7]. A strong awareness of antimicrobial resistance has been observed among German General Practitioners (GPs), while measures to improve rational prescribing were found to be not widely implemented [8]. In more recent research, it was found that the use of antibiotics in German primary care showed large variations between and within medical specialties and season and that a considerable proportion of antibiotic prescriptions lacked conformity with national guideline recommendations [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we systematically examined whether the prescription of the most commonly used phytopharmaceuticals to treat acute lower and upper tract respiratory infections is associated with lower antibiotic use as the disease progresses. Since the duration of the disease is a common reason for prescribing antibiotics [18,19], we also examined the effects of the use of phytopharmaceuticals on the duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The CHANGE-3 study was one of a number of efforts to change habits of the use of antibiotics in German primary care conducted in recent years. Other studies focused on knowledge about factors causing antimicrobial resistance and strategies like delayed prescribing [25], online education on provider-patient-communication [26], attitudes and perceptions to antimicrobial resistances and preferred information sources [27] or used complex implementation programs to promote the rational use of antibiotics in primary care networks [28]. Impulses for primary care gained in these studies were collated in a recent symposium [29].…”
Section: Discussionmentioning
confidence: 99%